APLIKASI PENCARIAN TEMPAT WISATA KULINER DI KOTA PEKALONGAN BERBASIS LOCATION BASED SERVICE DAN GEOTAGGING PADA ANDROID - Taryadi, Taryadi (BAPPEDA Kota Pekalongan, 2016)
PEKALONGAN AS ONE OF THE TOURIST CITY HAS CULINARY DESTINATION FAVORED BY MANYTOURISTS.THEREFORE, CULINARY DESTINATION SEARCH TOOL IS NEEDED BY THEM. THIS RESEARCH DEVELOPEDAN APPLICATION TO FINDCULINARY DESTINATIONS BASED ON LOCATION BASED SERVICE (LBS) AND GEOTAGGING ON ANDROID. APPLICATION DEVELOPED IN THIS RESEARCH HAS 9 FUNCTIONAL REQUIREMENTS WHICH ARE: VIEW MAP OF CULINARY DESTINATIONS, VIEW LIST OF NEARBY RESTAURANTS, VIEW LIST OF ALL RESTAURANTS/CULINARYMENUS, SEARCH RESTAURANT/CULINARY MENU, VIEW DETAILS OF RESTAURANTS/CULINARY MENUS, ADD DATA RESTAURANT/CULINARY MENU USING GEOTAGGING PHOTO, DISPLAY TRAVEL ROUTE, RATE RESTAURANT/CULINARY MENU, AND SET TYPE OF MAP VIEW. THIS APPLICATION USED GOOGLE API AS THE MAP AND ROUTE PROVIDER TO DIRECT USER TO THE CULINARY LOCATION. THIS APPLICATION ALSO IMPLEMENTED GEOTAGGING TO ADD LOCATION DATA TO THE SERVER. USABILITY EVALUATION ON THE SYSTEM USING QUESTIONNAIRE YIELDED VALUE OF 84.78%.